Impact of High Performance Work Practices on Employee Engagement in Apparel Manufacturing and Retail Firms - Regy, Joseph; Malini, D. H. (Prabandhan: Indian Journal of Management, 2019)
This study explored the relation of high-performance work practices with employee engagement in apparel manufacturing and retail sector. The data were collected from 150 employees of apparel manufacturing and retail companies in Bangalore through a questionnaire survey. Data collected were run through factor analysis and regression. The results were in the expected direction and fulfilled the research aims of the current study. During factor analysis, five major factors emerged with high factor loadings from 0.40 to 0.80. High factor loadings were indicative of high engagement levels due to human resources (HR) practices followed. Companies can continue with HR practices, which makes them good places to work for employees and practice good leadership to motivate people to join the apparel and retail sector, which has been facing challenging times.